PENERAPAN MEDIA ANIMASI MELALUI APLIKASI POWTOON UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - M Mahbubi; Zainatul Widad (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study is motivated by the need to enhance student engagement in Islamic Religious Education (PAI) learning through the use of technology-based learning media, specifically the Powtoon application. This research aims to describe the process and impact of using Powtoon on students' critical thinking, collaboration, and communication skills. The study employs a qualitative approach, utilizing a case study method, with eighth-grade students from a public junior high school as participants. Data were collected through direct observation during the learning process, in-depth interviews with students and teachers, and document analysis of students' work and projects. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to identify the main themes that emerged. The results show that the implementation of Powtoon encourages students to be more active in asking questions, exploring material, and expressing opinions. Collaborative activities increased as students engaged in designing animations together, while oral communication skills developed through presenting their work in front of the class. Both teachers and students also reported that the use of this media made PAI learning more engaging, interactive, and relevant to everyday life. These findings affirm that Powtoon can be an innovative and effective medium for teaching PAI, particularly in developing 21st-century skills. This study recommends integrating similar animation media into PAI teaching strategies to enhance the quality of the learning process and improve students' learning outcomes.